Improving Marketing Strategies Using a Clustering and AR-MBA Methods at Indomaret Kaliurang - Mukarim, Rifki Nurul; Subagja, Dandy Fri; Basuki, Demas Emirbuwono; Apriani, Ratna Agil (JTI: Jurnal Teknik Industri, 2024)
Marketing is the main activity carried out by entrepreneurs to maintain the viability of their business, develop the company, and get maximum profit. Companies need to know the right and appropriate marketing strategy so that the products to be sold on the market. Marketing strategy is one of the strategies applied to the retail industry in Indonesia, one of which is Indomaret. The purpose of this research is to increase market competitiveness so that it can survive and develop, and Indomaret in Kaliurang hopes to make a strategy to increase sales by conducting an analysis of consumer segments and product categories so that they can create sales strategies that can increase sales. The method used is clustering to find potential target markets that have similar characteristics and association rules &; Market basket analysis (AR-MBA) is used to find best practices for product marketing. The results of the Cluster Method with Non-Hierarchical Algorithm K-Means are 3 clusters. Based on the analysis conducted, it was found that the results of the AR-MBA method, there could be 6 rules for goods purchased simultaneously. Marketing strategies that can be applied by Indomaret Kaliurang such as promotions can be created by making products that are rarely purchased as bonuses for buying products that are often purchased. In addition, vouchers can be created as a promotional tool to encourage greater consumer purchases. Keywords: AR-MBA, clustering, sales strategy, strategy marketing